Handbook of hemodynamic monitoring - Darovic, Gloria Oblouk (Saunders, 2004)
In an easily accessible format, this new edition simply and comprehensively emphasizes the most relevant technical points and appropriate clinical applications of monitoring techniques. Readers will gain a sound, fundamental understanding of the anatomy and physiology of the cardiovascular and pulmonary systems. In addition, the text discusses important pathophysiologic, diagnostic, and management principles for common cardiopulmonary diseases, emphasizing the individuality of patient responses. The means of early detection and appropriate interventions of impending patient crisis are also discussed. With the information provided, readers will be able to correlate physical findings, monitoring information and laboratory data with the goal of formulating an effective, individualized, and precise management plan for high-risk perioperative, emergency, and ICU patients.